2019
DOI: 10.1111/gcb.14750
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term nitrogen addition modifies microbial composition and functions for slow carbon cycling and increased sequestration in tropical forest soil

Abstract: Nitrogen (N) deposition is a component of global change that has considerable impact on belowground carbon (C) dynamics. Plant growth stimulation and alterations of fungal community composition and functions are the main mechanisms driving soil C gains following N deposition in N-limited temperate forests. In N-rich tropical forests,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(73 citation statements)
references
References 99 publications
1
68
3
1
Order By: Relevance
“…Second, the microbial community plays an important role in this process of N addition, affecting SOC accumulation. Several recent studies have highlighted the important role of the bacterial community in determining the SOC content [13,26,33]. The SYMPHONY model also indicated that atmospheric N deposition may promote SOC accumulation via changes in the structure and metabolic activities of microbial communities [34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, the microbial community plays an important role in this process of N addition, affecting SOC accumulation. Several recent studies have highlighted the important role of the bacterial community in determining the SOC content [13,26,33]. The SYMPHONY model also indicated that atmospheric N deposition may promote SOC accumulation via changes in the structure and metabolic activities of microbial communities [34].…”
Section: Discussionmentioning
confidence: 99%
“…N addition changes microbial degradation, alters the molecular composition of SOM, and enhances soil carbon storage. Bacterial community structure was reported to be related to SOC decomposition under high N addition [13,16], indicating the key mechanisms driving SOC accumulation. Under high N addition, soil acidification and the available N content increased, and the dominance of a few bacteria, such as Proteobacteria, increased in the bacterial community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 50 year fertilization experiment reported that the size of functional guilds involved in N cycling was greatly affected by N input, and the size of the functional guilds correlated well with corresponding biogeochemical processes (Hallin, Jones, Schloter, & Philippot, 2009). Tian et al (2019) demonstrated that N deposition in a long-term experiment of tropical forest soil profoundly affected biogeochemical cycling by affecting the expression of microbial functional genes. This study identified important associations between the responses of soil microbial functional potentials and the cycling of soil nutrients (C, N, and P) to the anthropogenic input of N in "pristine" tropical forests.…”
Section: An Investigation Of Watersheds In a Remote Area Of The Northernmentioning
confidence: 99%